Benchmarking innovations and new practices in rural tourism development: How do we develop a more sustainable and responsible rural tourism in Asia? - Vikneswaran, Nair; Kashif, Hussain; Lo, May Chiun; Neethiahnanthan, Ari Ragavan (Emerald Group Publishing Limited, 2015)
responding to the strategic question: “How do we develop more sustainable and responsible rural tourism by benchmarking innovations and new practices in Asia?” Design/methodology/approach – A content analysis of the papers was undertaken to learn from best practices within and outside Asia. Structured questions were used to enable the theme editors to reflect on the rationale for the theme issue question, the starting point and the nature of the contribution made by the writing team. Findings – This summary highlights the most significant outcomes in terms of the contributions to knowledge and/or professional practice, and also the implications for management action and applied research arising from the review of best practices in Asian countries such as Malaysia, Indonesia, Thailand, The Philippines, Vietnam, Korea, India, China and Chinese Taipei. Some of the innovative approaches that can be adopted by Asia from non-Asian countries, namely, New Zealand, Australia, Canada, Lesotho and Poland, are also presented. Research limitations/implications – This paper outlines the challenges and new approaches needed in managing and developing rural tourism initiatives that have been established in other countries. Originality/value – This paper explores the extent to which the lessons and innovative approaches discussed in this theme issue could be replicated and applied in countries that are developing rural tourism.